Les organisations internationales du Tiers Monde : Vers l’élaboration d’un nouveau cadre d’analyse - Braillard, Philippe; Djalili, Mohammad-Reza (Études internationales, 1985)
The article outlines broad directions for the elaboration of a model that could be used to demonstrate the specificity of Third World international organizations. The first section deals with the specific nature of these organizations' environment. The article then define the mechanisms which are at the basis of their development. The recognition of the specific nature of Third World international organizations leads to the conclusion that political factors play an essential role in the birth, operation and sometimes failure of these organizations. In the Third World, international organizations are essentially a political phenomenon, combining powers which, because of the existence of few or none real functional needs, can hardly go beyond their immediate interests to work toward the strengthening of structures of international cooperation, which effects can only be felt in the middle or long term.